The journey continues - Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2015)
Here is the second special issue of the journal Acta BioMedica, dedicated to the health professions. The publication of the first issue gave rise to diverse reactions - all positive - in the relevant circles. [...]